الديـن من منظور سوسيولوجي - فيلالـي, صـالح (Sciences de l'Homme et de la Société, 2014)
هدفت هذه الدراسة الى بحث العلاقة بين الدين والمجتمع وتبيان أهمية الدين في حياة الأفراد والجماعات. استعرض المقال في البداية المفاهيم السوسيولوجية للدين من وجهات نظرمختلفة كالتطورية، الماركسية، الوظيفية والفيبيرية، مبيناً أوجه التشابه والاختلاف بينها من حيث التعريف والمعالجة المنهجية. كما ناقش المقال أيضا العلاقة بين الدين والعلمانية في المجتمعات الغربية من جهة، وعلم اجتماع المعرفة من جهة ثانية، وخلص إلى القول بأن هناك عودة صريحة إلى الممارسات الدينية في تلك المجتمعات التي يعتقد البعض أنها وسيلة للتخلص من بعض الإفرازات السلبية لتطور الحضارة الغربية، خاصة فيما يتعلق بالمسائل الأخلاقية والانحرافات الاجتماعية التي بدأت تنخر جسم المجتمعات الغربية.   The aim of this article is to examine the relationship between religion and society and to demonstrate the importance of religion in people’s lives . It viewed initially the main definitions of the concept of religion and analyzed  in detail the religious phenomenon from different sociological perspectives. The article also discussed the relationship between religion and secularism in western society and showed that there is an explicit return to religious practices in those societies which some believe it is a way to get rid of some of the negative secretions of the evolution of western civilization, especially those related to moral deviations and social ills. The article also discussed the relationship between religion and sociology of knowledge.